Modified Huangqi Shengmai Yin enhances ruminal microbiome and metabolites activity in dairy cows with subclinical mastitis - Chenyibo Zhang; Baoling Zhang; Yuqiong Li; John P. Kastelic; Xiaoping Li; Xiaofang Tong; A. Yao; Chuang Xu; Bo Han; Jian Gao (Frontiers in Veterinary Science)
IntroductionBovine mastitis, especially subclinical mastitis (SCM), with minimal clinical signs, is detrimental due to its resistance to treatment, recurrence, and substantial economic impact on global dairy industry. The modified form of Huangqi Shengmai Yin (HSY), classical traditional herbal medicine renowned for its effects in antimicrobial and circulatory-enhancing and thus beneficial for subclinical mastitis, has been developed for treatment attempt of SCM, yet its therapeutic effect and mechanism remains unclear. This study aims to investigate the therapeutic effects of mHSY on SCM in cows, and elucidate its potential therapeutic mechanism.MethodsIn this study, mHSY was given orally to cows with SCM. After a 3-day treatment regimen, the therapeutic effects were evaluated. 16S diversity sequencing and metabolomics were used to elucidate the therapeutic mechanism of HSY.ResultsThe SCM was significantly alleviated after the 3-day treatment with HSY. In cows infected with SCM, there were significant alterations in rumen fluid microbiota, particularly proportions of Enterobacter, Desulfovibrio, and Flavonifractor, implying a pivotal role for these bacteria in SCM. Furthermore, the therapeutic potential of HSY is linked to improving the proportion of beneficial bacteria (e.g., Succinivibrionaceae_UCG-001) and re-establishing a balanced ruminal bacterial profile. Modulation of fatty acid and amino acid metabolism, as evidenced by changes in metabolite profiles, is a critical aspect of SCM and can be markedly ameliorated with mHSY administration.ConclusionmHSY shows significant inhibitory effects on SCM, which may be attributed to regulating ruminal microbiota and metabolic pathways in vivo.